A new record of Polistella (Polistes) species (Hymenoptera: Vespidae: Polistinae) with its nest description from Tay Nguyen plateau, Vietnam - Phuong Lien, Nguyen Thi (Academia Journal of Biology, 2015)
One social wasp species of subgenus Polistella of the genus Polistes (Hymenoptera: Vespidae: Polistinae), Polistes meadeanus (von Schulthess), is recorded from Tay Nguyen plateau of Vietnam for the first time. This species can be distinguished from all other known species of subgenus Polistella from Vietnam by the metasomal tergum I distinctly longer than its apical width (1.4:1), and petiole of the nest is central, not terminal like almost other Polistella species. Nest structure of the species is also described in detail. Figures of female, male and nest are presented. The reported distribution areas of the species are confined to southern parts of the Southeast Asia, or Sundaland and the southeastern part of Indochina, and in this paper it is recorded from mainland for the first time. This record gives a great contribution to our knowledge on the distribution of the species, and supports to the hypothesis of the origin of the species, its origin is possibly in Sundaland with subsequent northward dispersal to Vietnam, but the Indochina origins and subsequent southward dispersal is not rejected.